Perlindungan Konsumen Terhadap Peredaran Rokok Ilegal Perspektif Ibnu Taimiyah di Kecamatan Berampu Kabupaten Dairi - Adzan Fikri Kabeakan; Sahliah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The circulation of illegal cigarettes in Berampu has become a significant issue, negatively impacting state revenues and public health. Illegal cigarettes that do not meet excise standards cause substantial economic losses and place consumers at risk due to unregulated product quality. This article analyzes consumer protection against the circulation of illegal cigarettes from the perspective of positive law and the teachings of Ibn Taymiyyah. Through a normative approach, this study highlights the importance of enforcing excise regulations as a consumer protection instrument and the relevance of principles of justice in trade transactions according to Ibn Taymiyyah. Ibn Taymiyyah emphasizes the importance of transparency, honesty, and justice in trade, aligning with modern regulatory objectives to protect consumers from fraud and harmful products. The study concludes that consumer protection from illegal cigarettes must involve synergy between strict law enforcement, public education, and the application of strong moral values as outlined in Islamic teachings. This synergy is expected to provide a comprehensive solution in efforts to curb the circulation of illegal cigarettes in Indonesia.